Late‐onset severe long QT syndrome. Issue 4 (30th November 2017) - Asatryan, Babken; Schaller, André; Bartholdi, Deborah; Medeiros‐Domingo, Argelia
Abstract : We report a case of torsades de pointes arrhythmia as the first manifestation of congenital Long QT syndrome in a 77‐year‐old man with family history of sudden unexplained death. This case illustrates the importance of vigilant clinical assessment and genetic counseling in families with sudden death in order to identify properly asymptomatic relatives at risk for cardiac events. It also demonstrates that Long QT syndrome can still manifest with potentially fatal arrhythmias late in life in previously asymptomatic elderly patients.